2015
DOI: 10.15193/zntj/2015/102/079
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Content of Free Fat During Egg Pasta Manufacturing Process

Abstract: Celem pracy było określenie wpływu procesu produkcji makaronu 4-jajecznego na stopień wiązania tłuszczu przez polisacharydy i białka zawarte w półproduktach i w produkcie finalnym. Makaron produkowano w warunkach przemysłowych na linii typu C300 metodą ekstruzji niskotemperaturowej. Dodatkowo, w celu porównania, przygotowano makaron z ciasta ręcznie zagniecionego i walcowanego. W próbkach mąki, ciasta i makaronów, pobieranych na kolejnych etapach produkcji, oznaczano zawartość tłuszczu wolnego (ekstrahowanego … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 16 publications
2
5
0
Order By: Relevance
“…According to Polish standards (PN-A-74131:1999), eggless common wheat pasta should contain approx. 0.4% free fat, while adding each egg should increase this value by approximately 0.5% (Sobota et al, 2015b). As expected, the samples of pasta with added eggs showed a significant increase in the free fat content; however, these values are lower than those assumed by the Polish standards.…”
Section: Chemical Composition Of Pastasupporting
confidence: 71%
“…According to Polish standards (PN-A-74131:1999), eggless common wheat pasta should contain approx. 0.4% free fat, while adding each egg should increase this value by approximately 0.5% (Sobota et al, 2015b). As expected, the samples of pasta with added eggs showed a significant increase in the free fat content; however, these values are lower than those assumed by the Polish standards.…”
Section: Chemical Composition Of Pastasupporting
confidence: 71%
“…to Polish standards (PN-A-74131:1999), eggless common wheat pasta should contain approx. 0.4% free fat, while adding each egg should increase this value by approximately 0.5% (Sobota et al, 2015b). As expected, the samples of pasta with added eggs showed a significant increase in the free fat content; however, these values are lower than those assumed by the Polish standards.…”
Section: Chemical Composition Of Pastasupporting
confidence: 71%
“…High levels of gluten proteins, which form a strong matrix, limit the access of water to the starch, thus prolonging the time of starch gelatinization. It may also be influenced by the thicker granulation of semolina (Grant et al, 1993;Sobota et al, 2015b). Each egg added also prolonged the cooking time by improving the continuity of the proteinstarch matrix.…”
Section: Cooking Quality Of Pastamentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast, the stable protein content of pasta with freeze-dried red potato pulp is most likely due to the fact that the freeze-dried potato pulp itself has a fairly high protein content of 11.32% (Table 3). Such a high protein content of 13% and above is, according to many authors, an indicator of good quality pasta [26][27][28]. Oak et al [29] reported that the high protein content of pasta has the following effects: reducing the susceptibility to overcooking, reducing dry matter loss during cooking, improving firmness and reducing the stickiness of the surface of the products after cooking.…”
Section: Effect Of Freeze-dried Red Potato Pulp and Cherry Pomace On ...mentioning
confidence: 99%